Theory Presburger

(* Title:      HOL/Presburger.thy
   Author:     Amine Chaieb, TU Muenchen
*)

section ‹Decision Procedure for Presburger Arithmetic›

theory Presburger
imports Groebner_Basis Set_Interval
keywords "try0" :: diag
begin

ML_file ‹Tools/Qelim/qelim.ML›
ML_file ‹Tools/Qelim/cooper_procedure.ML›

subsection‹The -∞› and +∞› Properties›

lemma minf:
  "(z ::'a::linorder).x<z. P x = P' x; z.x<z. Q x = Q' x 
      z.x<z. (P x  Q x) = (P' x  Q' x)"
  "(z ::'a::linorder).x<z. P x = P' x; z.x<z. Q x = Q' x 
      z.x<z. (P x  Q x) = (P' x  Q' x)"
  "(z ::'a::{linorder}).x<z.(x = t) = False"
  "(z ::'a::{linorder}).x<z.(x  t) = True"
  "(z ::'a::{linorder}).x<z.(x < t) = True"
  "(z ::'a::{linorder}).x<z.(x  t) = True"
  "(z ::'a::{linorder}).x<z.(x > t) = False"
  "(z ::'a::{linorder}).x<z.(x  t) = False"
  "z.(x::'b::{linorder,plus,Rings.dvd})<z. (d dvd x + s) = (d dvd x + s)"
  "z.(x::'b::{linorder,plus,Rings.dvd})<z. (¬ d dvd x + s) = (¬ d dvd x + s)"
  "z.x<z. F = F"
  by ((erule exE, erule exE,rule_tac x="min z za" in exI,simp)+, (rule_tac x="t" in exI,fastforce)+) simp_all

lemma pinf:
  "(z ::'a::linorder).x>z. P x = P' x; z.x>z. Q x = Q' x 
      z.x>z. (P x  Q x) = (P' x  Q' x)"
  "(z ::'a::linorder).x>z. P x = P' x; z.x>z. Q x = Q' x 
      z.x>z. (P x  Q x) = (P' x  Q' x)"
  "(z ::'a::{linorder}).x>z.(x = t) = False"
  "(z ::'a::{linorder}).x>z.(x  t) = True"
  "(z ::'a::{linorder}).x>z.(x < t) = False"
  "(z ::'a::{linorder}).x>z.(x  t) = False"
  "(z ::'a::{linorder}).x>z.(x > t) = True"
  "(z ::'a::{linorder}).x>z.(x  t) = True"
  "z.(x::'b::{linorder,plus,Rings.dvd})>z. (d dvd x + s) = (d dvd x + s)"
  "z.(x::'b::{linorder,plus,Rings.dvd})>z. (¬ d dvd x + s) = (¬ d dvd x + s)"
  "z.x>z. F = F"
  by ((erule exE, erule exE,rule_tac x="max z za" in exI,simp)+,(rule_tac x="t" in exI,fastforce)+) simp_all

lemma inf_period:
  "x k. P x = P (x - k*D); x k. Q x = Q (x - k*D) 
     x k. (P x  Q x) = (P (x - k*D)  Q (x - k*D))"
  "x k. P x = P (x - k*D); x k. Q x = Q (x - k*D) 
     x k. (P x  Q x) = (P (x - k*D)  Q (x - k*D))"
  "(d::'a::{comm_ring,Rings.dvd}) dvd D  x k. (d dvd x + t) = (d dvd (x - k*D) + t)"
  "(d::'a::{comm_ring,Rings.dvd}) dvd D  x k. (¬d dvd x + t) = (¬d dvd (x - k*D) + t)"
  "x k. F = F"
apply (auto elim!: dvdE simp add: algebra_simps)
unfolding mult.assoc [symmetric] distrib_right [symmetric] left_diff_distrib [symmetric]
unfolding dvd_def mult.commute [of d] 
by auto

subsection‹The A and B sets›
lemma bset:
  "x.(j  {1 .. D}. bB. x  b + j) P x  P(x - D) ;
     x.(j{1 .. D}. bB. x  b + j) Q x  Q(x - D)  
  x.(j{1 .. D}. bB. x  b + j)  (P x  Q x)  (P(x - D)  Q (x - D))"
  "x.(j{1 .. D}. bB. x  b + j) P x  P(x - D) ;
     x.(j{1 .. D}. bB. x  b + j) Q x  Q(x - D)  
  x.(j{1 .. D}. bB. x  b + j) (P x  Q x)  (P(x - D)  Q (x - D))"
  "D>0; t - 1 B  (x.(j{1 .. D}. bB. x  b + j) (x = t)  (x - D = t))"
  "D>0 ; t  B ((x::int).(j{1 .. D}. bB. x  b + j) (x  t)  (x - D  t))"
  "D>0  ((x::int).(j{1 .. D}. bB. x  b + j) (x < t)  (x - D < t))"
  "D>0  ((x::int).(j{1 .. D}. bB. x  b + j) (x  t)  (x - D  t))"
  "D>0 ; t  B ((x::int).(j{1 .. D}. bB. x  b + j) (x > t)  (x - D > t))"
  "D>0 ; t - 1  B ((x::int).(j{1 .. D}. bB. x  b + j) (x  t)  (x - D  t))"
  "d dvd D ((x::int).(j{1 .. D}. bB. x  b + j) (d dvd x+t)  (d dvd (x - D) + t))"
  "d dvd D ((x::int).(j{1 .. D}. bB. x  b + j) (¬d dvd x+t)  (¬ d dvd (x - D) + t))"
  "x.(j{1 .. D}. bB. x  b + j)  F  F"
proof (blast, blast)
  assume dp: "D > 0" and tB: "t - 1 B"
  show "(x.(j{1 .. D}. bB. x  b + j) (x = t)  (x - D = t))" 
    apply (rule allI, rule impI,erule ballE[where x="1"],erule ballE[where x="t - 1"]) 
    apply algebra using dp tB by simp_all
next
  assume dp: "D > 0" and tB: "t  B"
  show "(x.(j{1 .. D}. bB. x  b + j) (x  t)  (x - D  t))" 
    apply (rule allI, rule impI,erule ballE[where x="D"],erule ballE[where x="t"])
    apply algebra
    using dp tB by simp_all
next
  assume dp: "D > 0" thus "(x.(j{1 .. D}. bB. x  b + j) (x < t)  (x - D < t))" by arith
next
  assume dp: "D > 0" thus "x.(j{1 .. D}. bB. x  b + j) (x  t)  (x - D  t)" by arith
next
  assume dp: "D > 0" and tB:"t  B"
  {fix x assume nob: "j{1 .. D}. bB. x  b + j" and g: "x > t" and ng: "¬ (x - D) > t"
    hence "x -t  D" and "1  x - t" by simp+
      hence "j  {1 .. D}. x - t = j" by auto
      hence "j  {1 .. D}. x = t + j" by (simp add: algebra_simps)
      with nob tB have "False" by simp}
  thus "x.(j{1 .. D}. bB. x  b + j) (x > t)  (x - D > t)" by blast
next
  assume dp: "D > 0" and tB:"t - 1 B"
  {fix x assume nob: "j{1 .. D}. bB. x  b + j" and g: "x  t" and ng: "¬ (x - D)  t"
    hence "x - (t - 1)  D" and "1  x - (t - 1)" by simp+
      hence "j  {1 .. D}. x - (t - 1) = j" by auto
      hence "j  {1 .. D}. x = (t - 1) + j" by (simp add: algebra_simps)
      with nob tB have "False" by simp}
  thus "x.(j{1 .. D}. bB. x  b + j) (x  t)  (x - D  t)" by blast
next
  assume d: "d dvd D"
  {fix x assume H: "d dvd x + t" with d have "d dvd (x - D) + t" by algebra}
  thus "(x::int).(j{1 .. D}. bB. x  b + j) (d dvd x+t)  (d dvd (x - D) + t)" by simp
next
  assume d: "d dvd D"
  {fix x assume H: "¬(d dvd x + t)" with d have "¬ d dvd (x - D) + t"
      by (clarsimp simp add: dvd_def,erule_tac x= "ka + k" in allE,simp add: algebra_simps)}
  thus "(x::int).(j{1 .. D}. bB. x  b + j) (¬d dvd x+t)  (¬d dvd (x - D) + t)" by auto
qed blast

lemma aset:
  "x.(j{1 .. D}. bA. x  b - j) P x  P(x + D) ;
     x.(j{1 .. D}. bA. x  b - j) Q x  Q(x + D)  
  x.(j{1 .. D}. bA. x  b - j)  (P x  Q x)  (P(x + D)  Q (x + D))"
  "x.(j{1 .. D}. bA. x  b - j) P x  P(x + D) ;
     x.(j{1 .. D}. bA. x  b - j) Q x  Q(x + D)  
  x.(j{1 .. D}. bA. x  b - j) (P x  Q x)  (P(x + D)  Q (x + D))"
  "D>0; t + 1 A  (x.(j{1 .. D}. bA. x  b - j) (x = t)  (x + D = t))"
  "D>0 ; t  A ((x::int).(j{1 .. D}. bA. x  b - j) (x  t)  (x + D  t))"
  "D>0; t A ((x::int). (j{1 .. D}. bA. x  b - j) (x < t)  (x + D < t))"
  "D>0; t + 1  A  ((x::int).(j{1 .. D}. bA. x  b - j) (x  t)  (x + D  t))"
  "D>0 ((x::int).(j{1 .. D}. bA. x  b - j) (x > t)  (x + D > t))"
  "D>0 ((x::int).(j{1 .. D}. bA. x  b - j) (x  t)  (x + D  t))"
  "d dvd D ((x::int).(j{1 .. D}. bA. x  b - j) (d dvd x+t)  (d dvd (x + D) + t))"
  "d dvd D ((x::int).(j{1 .. D}. bA. x  b - j) (¬d dvd x+t)  (¬ d dvd (x + D) + t))"
  "x.(j{1 .. D}. bA. x  b - j)  F  F"
proof (blast, blast)
  assume dp: "D > 0" and tA: "t + 1  A"
  show "(x.(j{1 .. D}. bA. x  b - j) (x = t)  (x + D = t))" 
    apply (rule allI, rule impI,erule ballE[where x="1"],erule ballE[where x="t + 1"])
    using dp tA by simp_all
next
  assume dp: "D > 0" and tA: "t  A"
  show "(x.(j{1 .. D}. bA. x  b - j) (x  t)  (x + D  t))" 
    apply (rule allI, rule impI,erule ballE[where x="D"],erule ballE[where x="t"])
    using dp tA by simp_all
next
  assume dp: "D > 0" thus "(x.(j{1 .. D}. bA. x  b - j) (x > t)  (x + D > t))" by arith
next
  assume dp: "D > 0" thus "x.(j{1 .. D}. bA. x  b - j) (x  t)  (x + D  t)" by arith
next
  assume dp: "D > 0" and tA:"t  A"
  {fix x assume nob: "j{1 .. D}. bA. x  b - j" and g: "x < t" and ng: "¬ (x + D) < t"
    hence "t - x  D" and "1  t - x" by simp+
      hence "j  {1 .. D}. t - x = j" by auto
      hence "j  {1 .. D}. x = t - j" by (auto simp add: algebra_simps) 
      with nob tA have "False" by simp}
  thus "x.(j{1 .. D}. bA. x  b - j) (x < t)  (x + D < t)" by blast
next
  assume dp: "D > 0" and tA:"t + 1 A"
  {fix x assume nob: "j{1 .. D}. bA. x  b - j" and g: "x  t" and ng: "¬ (x + D)  t"
    hence "(t + 1) - x  D" and "1  (t + 1) - x" by (simp_all add: algebra_simps)
      hence "j  {1 .. D}. (t + 1) - x = j" by auto
      hence "j  {1 .. D}. x = (t + 1) - j" by (auto simp add: algebra_simps)
      with nob tA have "False" by simp}
  thus "x.(j{1 .. D}. bA. x  b - j) (x  t)  (x + D  t)" by blast
next
  assume d: "d dvd D"
  {fix x assume H: "d dvd x + t" with d have "d dvd (x + D) + t"
      by (clarsimp simp add: dvd_def,rule_tac x= "ka + k" in exI,simp add: algebra_simps)}
  thus "(x::int).(j{1 .. D}. bA. x  b - j) (d dvd x+t)  (d dvd (x + D) + t)" by simp
next
  assume d: "d dvd D"
  {fix x assume H: "¬(d dvd x + t)" with d have "¬d dvd (x + D) + t"
      by (clarsimp simp add: dvd_def,erule_tac x= "ka - k" in allE,simp add: algebra_simps)}
  thus "(x::int).(j{1 .. D}. bA. x  b - j) (¬d dvd x+t)  (¬d dvd (x + D) + t)" by auto
qed blast

subsection‹Cooper's Theorem -∞› and +∞› Version›

subsubsection‹First some trivial facts about periodic sets or predicates›
lemma periodic_finite_ex:
  assumes dpos: "(0::int) < d" and modd: "x k. P x = P(x - k*d)"
  shows "(x. P x) = (j  {1..d}. P j)"
  (is "?LHS = ?RHS")
proof
  assume ?LHS
  then obtain x where P: "P x" ..
  have "x mod d = x - (x div d)*d" by(simp add:mult_div_mod_eq [symmetric] ac_simps eq_diff_eq)
  hence Pmod: "P x = P(x mod d)" using modd by simp
  show ?RHS
  proof (cases)
    assume "x mod d = 0"
    hence "P 0" using P Pmod by simp
    moreover have "P 0 = P(0 - (-1)*d)" using modd by blast
    ultimately have "P d" by simp
    moreover have "d  {1..d}" using dpos by simp
    ultimately show ?RHS ..
  next
    assume not0: "x mod d  0"
    have "P(x mod d)" using dpos P Pmod by simp
    moreover have "x mod d  {1..d}"
    proof -
      from dpos have "0  x mod d" by(rule pos_mod_sign)
      moreover from dpos have "x mod d < d" by(rule pos_mod_bound)
      ultimately show ?thesis using not0 by simp
    qed
    ultimately show ?RHS ..
  qed
qed auto

subsubsection‹The -∞› Version›

lemma decr_lemma: "0 < (d::int)  x - (¦x - z¦ + 1) * d < z"
  by (induct rule: int_gr_induct) (simp_all add: int_distrib)

lemma incr_lemma: "0 < (d::int)  z < x + (¦x - z¦ + 1) * d"
  by (induct rule: int_gr_induct) (simp_all add: int_distrib)

lemma decr_mult_lemma:
  assumes dpos: "(0::int) < d" and minus: "x. P x  P(x - d)" and knneg: "0 <= k"
  shows "x. P x  P(x - k*d)"
using knneg
proof (induct rule:int_ge_induct)
  case base thus ?case by simp
next
  case (step i)
  {fix x
    have "P x  P (x - i * d)" using step.hyps by blast
    also have "  P(x - (i + 1) * d)" using minus[THEN spec, of "x - i * d"]
      by (simp add: algebra_simps)
    ultimately have "P x  P(x - (i + 1) * d)" by blast}
  thus ?case ..
qed

lemma  minusinfinity:
  assumes dpos: "0 < d" and
    P1eqP1: "x k. P1 x = P1(x - k*d)" and ePeqP1: "z::int. x. x < z  (P x = P1 x)"
  shows "(x. P1 x)  (x. P x)"
proof
  assume eP1: "x. P1 x"
  then obtain x where P1: "P1 x" ..
  from ePeqP1 obtain z where P1eqP: "x. x < z  (P x = P1 x)" ..
  let ?w = "x - (¦x - z¦ + 1) * d"
  from dpos have w: "?w < z" by(rule decr_lemma)
  have "P1 x = P1 ?w" using P1eqP1 by blast
  also have " = P(?w)" using w P1eqP by blast
  finally have "P ?w" using P1 by blast
  thus "x. P x" ..
qed

lemma cpmi: 
  assumes dp: "0 < D" and p1:"z.  x< z. P x = P' x"
  and nb:"x.( j {1..D}. (b::int)  B. x  b+j)  P (x)  P (x - D)"
  and pd: " x k. P' x = P' (x-k*D)"
  shows "(x. P x) = ((j  {1..D} . P' j)  (j  {1..D}.  b  B. P (b+j)))"
         (is "?L = (?R1  ?R2)")
proof-
 {assume "?R2" hence "?L"  by blast}
 moreover
 {assume H:"?R1" hence "?L" using minusinfinity[OF dp pd p1] periodic_finite_ex[OF dp pd] by simp}
 moreover 
 { fix x
   assume P: "P x" and H: "¬ ?R2"
   {fix y assume "¬ (j{1..D}. bB. P (b + j))" and P: "P y"
     hence "¬((j::int)  {1..D}. (b::int)  B. y = b+j)" by auto
     with nb P  have "P (y - D)" by auto }
   hence "x. ¬((j::int)  {1..D}. (b::int)  B. P(b+j))  P (x)  P (x - D)" by blast
   with H P have th: " x. P x  P (x - D)" by auto
   from p1 obtain z where z: "x. x < z  (P x = P' x)" by blast
   let ?y = "x - (¦x - z¦ + 1)*D"
   have zp: "0 <= (¦x - z¦ + 1)" by arith
   from dp have yz: "?y < z" using decr_lemma[OF dp] by simp   
   from z[rule_format, OF yz] decr_mult_lemma[OF dp th zp, rule_format, OF P] have th2: " P' ?y" by auto
   with periodic_finite_ex[OF dp pd]
   have "?R1" by blast}
 ultimately show ?thesis by blast
qed

subsubsection ‹The +∞› Version›

lemma  plusinfinity:
  assumes dpos: "(0::int) < d" and
    P1eqP1: "x k. P' x = P'(x - k*d)" and ePeqP1: " z.  x>z. P x = P' x"
  shows "( x. P' x)  ( x. P x)"
proof
  assume eP1: "x. P' x"
  then obtain x where P1: "P' x" ..
  from ePeqP1 obtain z where P1eqP: "x>z. P x = P' x" ..
  let ?w' = "x + (¦x - z¦ + 1) * d"
  let ?w = "x - (- (¦x - z¦ + 1)) * d"
  have ww'[simp]: "?w = ?w'" by (simp add: algebra_simps)
  from dpos have w: "?w > z" by(simp only: ww' incr_lemma)
  hence "P' x = P' ?w" using P1eqP1 by blast
  also have " = P(?w)" using w P1eqP by blast
  finally have "P ?w" using P1 by blast
  thus "x. P x" ..
qed

lemma incr_mult_lemma:
  assumes dpos: "(0::int) < d" and plus: "x::int. P x  P(x + d)" and knneg: "0 <= k"
  shows "x. P x  P(x + k*d)"
using knneg
proof (induct rule:int_ge_induct)
  case base thus ?case by simp
next
  case (step i)
  {fix x
    have "P x  P (x + i * d)" using step.hyps by blast
    also have "  P(x + (i + 1) * d)" using plus[THEN spec, of "x + i * d"]
      by (simp add:int_distrib ac_simps)
    ultimately have "P x  P(x + (i + 1) * d)" by blast}
  thus ?case ..
qed

lemma cppi: 
  assumes dp: "0 < D" and p1:"z.  x> z. P x = P' x"
  and nb:"x.( j {1..D}. (b::int)  A. x  b - j)  P (x)  P (x + D)"
  and pd: " x k. P' x= P' (x-k*D)"
  shows "(x. P x) = ((j  {1..D} . P' j)  ( j  {1..D}.  b A. P (b - j)))" (is "?L = (?R1  ?R2)")
proof-
 {assume "?R2" hence "?L"  by blast}
 moreover
 {assume H:"?R1" hence "?L" using plusinfinity[OF dp pd p1] periodic_finite_ex[OF dp pd] by simp}
 moreover 
 { fix x
   assume P: "P x" and H: "¬ ?R2"
   {fix y assume "¬ (j{1..D}. bA. P (b - j))" and P: "P y"
     hence "¬((j::int)  {1..D}. (b::int)  A. y = b - j)" by auto
     with nb P  have "P (y + D)" by auto }
   hence "x. ¬((j::int)  {1..D}. (b::int)  A. P(b-j))  P (x)  P (x + D)" by blast
   with H P have th: " x. P x  P (x + D)" by auto
   from p1 obtain z where z: "x. x > z  (P x = P' x)" by blast
   let ?y = "x + (¦x - z¦ + 1)*D"
   have zp: "0 <= (¦x - z¦ + 1)" by arith
   from dp have yz: "?y > z" using incr_lemma[OF dp] by simp
   from z[rule_format, OF yz] incr_mult_lemma[OF dp th zp, rule_format, OF P] have th2: " P' ?y" by auto
   with periodic_finite_ex[OF dp pd]
   have "?R1" by blast}
 ultimately show ?thesis by blast
qed

lemma simp_from_to: "{i..j::int} = (if j < i then {} else insert i {i+1..j})"
apply(simp add:atLeastAtMost_def atLeast_def atMost_def)
apply(fastforce)
done

theorem unity_coeff_ex: "((x::'a::{semiring_0,Rings.dvd}). P (l * x))  (x. l dvd (x + 0)  P x)"
  apply (rule eq_reflection [symmetric])
  apply (rule iffI)
  defer
  apply (erule exE)
  apply (rule_tac x = "l * x" in exI)
  apply (simp add: dvd_def)
  apply (rule_tac x = x in exI, simp)
  apply (erule exE)
  apply (erule conjE)
  apply simp
  apply (erule dvdE)
  apply (rule_tac x = k in exI)
  apply simp
  done

lemma zdvd_mono:
  fixes k m t :: int
  assumes "k  0"
  shows "m dvd t  k * m dvd k * t" 
  using assms by simp

lemma uminus_dvd_conv:
  fixes d t :: int
  shows "d dvd t  - d dvd t" and "d dvd t  d dvd - t"
  by simp_all

text ‹\bigskip Theorems for transforming predicates on nat to predicates on int›

lemma zdiff_int_split: "P (int (x - y)) =
  ((y  x  P (int x - int y))  (x < y  P 0))"
  by (cases "y  x") (simp_all add: of_nat_diff)

text ‹
  \medskip Specific instances of congruence rules, to prevent
  simplifier from looping.›

theorem imp_le_cong:
  "x = x'; 0  x'  P = P'  (0  (x::int)  P) = (0  x'  P')"
  by simp

theorem conj_le_cong:
  "x = x'; 0  x'  P = P'  (0  (x::int)  P) = (0  x'  P')"
  by (simp cong: conj_cong)

ML_file ‹Tools/Qelim/cooper.ML›

method_setup presburger = let
    fun keyword k = Scan.lift (Args.$$$ k -- Args.colon) >> K ()
    fun simple_keyword k = Scan.lift (Args.$$$ k) >> K ()
    val addN = "add"
    val delN = "del"
    val elimN = "elim"
    val any_keyword = keyword addN || keyword delN || simple_keyword elimN
    val thms = Scan.repeats (Scan.unless any_keyword Attrib.multi_thm)
  in
    Scan.optional (simple_keyword elimN >> K false) true --
    Scan.optional (keyword addN |-- thms) [] --
    Scan.optional (keyword delN |-- thms) [] >>
    (fn ((elim, add_ths), del_ths) => fn ctxt =>
      SIMPLE_METHOD' (Cooper.tac elim add_ths del_ths ctxt))
  end "Cooper's algorithm for Presburger arithmetic"

declare mod_eq_0_iff_dvd [presburger]
declare mod_by_Suc_0 [presburger] 
declare mod_0 [presburger]
declare mod_by_1 [presburger]
declare mod_self [presburger]
declare div_by_0 [presburger]
declare mod_by_0 [presburger]
declare mod_div_trivial [presburger]
declare mult_div_mod_eq [presburger]
declare div_mult_mod_eq [presburger]
declare mod_mult_self1 [presburger]
declare mod_mult_self2 [presburger]
declare mod2_Suc_Suc [presburger]
declare not_mod_2_eq_0_eq_1 [presburger] 
declare nat_zero_less_power_iff [presburger]

lemma [presburger, algebra]: "m mod 2 = (1::nat)  ¬ 2 dvd m " by presburger
lemma [presburger, algebra]: "m mod 2 = Suc 0  ¬ 2 dvd m " by presburger
lemma [presburger, algebra]: "m mod (Suc (Suc 0)) = (1::nat)  ¬ 2 dvd m " by presburger
lemma [presburger, algebra]: "m mod (Suc (Suc 0)) = Suc 0  ¬ 2 dvd m " by presburger
lemma [presburger, algebra]: "m mod 2 = (1::int)  ¬ 2 dvd m " by presburger

context semiring_parity
begin

declare even_mult_iff [presburger]

declare even_power [presburger]

lemma [presburger]:
  "even (a + b)  even a  even b  odd a  odd b"
  by auto

end

context ring_parity
begin

declare even_minus [presburger]

end

context linordered_idom
begin

declare zero_le_power_eq [presburger]

declare zero_less_power_eq [presburger]

declare power_less_zero_eq [presburger]
  
declare power_le_zero_eq [presburger]

end

declare even_Suc [presburger]

lemma [presburger]:
  "Suc n div Suc (Suc 0) = n div Suc (Suc 0)  even n"
  by presburger

declare even_diff_nat [presburger]

lemma [presburger]:
  fixes k :: int
  shows "(k + 1) div 2 = k div 2  even k"
  by presburger

lemma [presburger]:
  fixes k :: int
  shows "(k + 1) div 2 = k div 2 + 1  odd k"
  by presburger

lemma [presburger]:
  "even n  even (int n)"
  by simp
  

subsection ‹Nice facts about division by term4  

lemma even_even_mod_4_iff:
  "even (n::nat)  even (n mod 4)"
  by presburger

lemma odd_mod_4_div_2:
  "n mod 4 = (3::nat)  odd ((n - Suc 0) div 2)"
  by presburger

lemma even_mod_4_div_2:
  "n mod 4 = Suc 0  even ((n - Suc 0) div 2)"
  by presburger


subsection ‹Try0›

ML_file ‹Tools/try0.ML›

end